Variations of crustal thickness and average Vp/Vs ratio beneath the Shanxi Rift, North China, from receiver functions - Chen, Yifang; Chen, Jiuhui; Li, ShunCheng; Yu, Zhanyang; Liu, Xuzhou; Shen, Xuzhang (Earth, planets, and space, 2021)
The Shanxi Rift located in the central part of the North China Craton (NCC) as a boundary between the Ordos block and the Huabei basin. The Shanxi graben system is a Cenozoic rift and originated from back-arc spreading related to westward subduction of the western Pacific and far field effects caused by northward subduction of the Indian plate. It has also had strong earthquake activity in China since the Quaternary. To investigate the tectonic evolution and tectonic setting of strong earthquakes in the Shanxi Rift, we apply the receiver function H - κ stacking method to determine the crustal thickness and average Vp/Vs ratio in the area. The results show that the thickness of the crust increases from approximately 30 km in the Huabei basin to approximately 47 km in the Yinshan Mountains with a close correlation between the Moho depth and topography. The Yuncheng, Linfen and Taiyuan grabens have varying degrees of crustal thinning. The crustal average Vp/Vs ratio in the Shanxi Rift has significant heterogeneity; the high Vp/Vs ratio (~ 1.85) are found in the Datong and Yuncheng grabens, and Vp/Vs ratio of the Taiyuan and Linfen grabens is approximately 1.75 which close to the global average value ~ 1.782. Combining the observations in this study with previous research, we suggest that the grabens in the Shanxi Rift experienced extensional deformation from south to north and that the possibility of strong earthquakes in the central part of the Shanxi seismic belt is greater than that on the northern and southern sides.